2021
DOI: 10.18502/ijhoscr.v15i4.7476
|View full text |Cite
|
Sign up to set email alerts
|

RHD Genotyping of Rh-Negative and Weak D Phenotype among Blood Donors in Southeast Iran

Abstract: Background: The D antigen is a subset of Rh blood group antigens involved in the hemolytic disease of the newborn [HDFN] and hemolytic transfusion reaction [HTR]. The hybrid Rhesus box that was created after RH gene deletion, was known as a mechanism of the Rh-negative phenotype. Hybrid marker identification is used to confirm the deletion of the RHD gene and to determine zygosity. This study aims to detect this marker in Rh-negative and weak D phenotype blood donors of the southeast of Iran. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A study conducted by Khosroshahi et al in 2019 in Iran on 200 RHD negative individuals showed that 99% of them were homozygous for the complete deletion of the RHD gene, and the remaining 1% could not be identified with the serological reagents used in that study due to weak and partial RHD variants ( 23 ). Also, in another study conducted in Iran in 2021 on 200 subjects, 99% of the RHD negative cases had the mechanism of homozygous deletion of the RHD gene and nonfunctional variants were observed in 1% of cases ( 24 ). These results suggest that RHD negative phenotype in the majority of individuals is the result of the deletion of the whole RHD gene, and the frequency of nonfunctional RHD variants, such as pseudogenes, is very low in the Iranian population, and they are very unlikely to be included in the study as RHD negative.…”
Section: Discussionmentioning
confidence: 96%
“…A study conducted by Khosroshahi et al in 2019 in Iran on 200 RHD negative individuals showed that 99% of them were homozygous for the complete deletion of the RHD gene, and the remaining 1% could not be identified with the serological reagents used in that study due to weak and partial RHD variants ( 23 ). Also, in another study conducted in Iran in 2021 on 200 subjects, 99% of the RHD negative cases had the mechanism of homozygous deletion of the RHD gene and nonfunctional variants were observed in 1% of cases ( 24 ). These results suggest that RHD negative phenotype in the majority of individuals is the result of the deletion of the whole RHD gene, and the frequency of nonfunctional RHD variants, such as pseudogenes, is very low in the Iranian population, and they are very unlikely to be included in the study as RHD negative.…”
Section: Discussionmentioning
confidence: 96%
“…The significance of RhD blood group in clinical blood transfusion is second only to ABO blood group. Severe transfusion reactions may occur if the blood of RhD positive or weak D donors is transfused into RhD negative donors 16 . Although the detection rate of UAb in the population is not high, it is one of the main reasons for HTRss, hemolytic disease of the fetus and newborn (HDFN), difficulty in blood group identification and in blood cross matching 17 .…”
Section: Discussionmentioning
confidence: 99%